"What the mind does not know, the eyes do not see". Placing food allergy risk in sub-Saharan Africa. (May 2018) - Atiim, George A.; Elliott, Susan J.; Clarke, Ann E.; Janes, Craig
Abstract: Policy makers and health geographers are increasingly intrigued by the global rise of chronic disease. While current engagement coalesce around cardiovascular disease, cancers, chronic respiratory disease, and diabetes, very little attention has been given to other important chronic conditions: e.g., allergic disease. Concerns about how health is shaped by context and experienced in place can provide important insights to understand the trajectory of allergic disease and inform policy especially in developing countries experiencing an epidemiologic transition. Using Ghana as a case study. this paper draw on theories of political ecology of health to enhance our understanding of how individual (e.g. care seeking behaviours), sociocultural (e.g. lack of education and awareness), health system (e.g. absence of logistics) and policy environments (e.g. absence of policy) influence the ways in which food allergy is perceived, diagnosed and managed. These findings highlight the need for decision makers to target structural factors that impede access to and utilization of healthcare, diagnostic practices, as well as food allergy coping and management strategies. Moreover, the findings highlight the need for a global health agenda that pays critical attention to place-based factors in the construction of emerging health risks. Highlights: Chronic disease is rising and a significant health issue in LMICs. To date research and policy neglect food allergic disease. We explore local-level factors shaping food allergy risk perceptions in Ghana. Risk perceptions are influence by sociocultural and political factors. Context is critical to understand the construction of emerging health risks.